Effectiveness of mechanical vibration-assisted sputum clearance in pediatric pneumonia: a randomized controlled trial with development of an intelligent parameter optimization model - Xue, Sujing; Lin, Kewu; Lin, Ledan; Zhou, Huijie; Dong, Lishuang; Chen, Huafen; Zhang, Tengfei (Frontiers in Pediatrics, 2025)
BackgroundSputum retention in pediatric pneumonia hinders recovery. This study evaluated the therapeutic benefits of incorporating mechanical vibration-assisted sputum clearance (MVSC) as an adjunct to standard pharmacological treatment and developed a nomogram to optimize treatment parameters.MethodsIn this randomized controlled trial, 160 children with pneumonia were randomly assigned (1:1) to a control group receiving pharmacological treatment or a treatment group receiving additional mechanical vibration therapy. The proportion of patients showing clinical improvement (defined as “markedly improved” or “improved”) was assessed, along with symptom resolution times, lung function, blood gas parameters, and inflammatory markers, which were measured at baseline and treatment completion. LASSO regression identified predictors of clinical improvement.ResultsA significantly greater proportion of patients exhibited clinical improvement in the treatment group (93.75%) compared to the control group (75%, P < 0.05). The treatment group also showed significantly shorter times for symptom resolution (pulmonary rales, fever, and cough) and hospital stay (P < 0.05). Improvements in lung function (FEV1, FEV1/FVC), blood gas parameters (PaO₂, PaCO₂, pH), and greater reductions in inflammatory markers (CRP, PCT), were observed in the treatment group (P < 0.05). A nomogram was developed using age, chest circumference, moist rales, disease severity, vibration frequency, and pressure to determine optimal mechanical vibration settings for individualized treatment. The nomogram showed high predictive accuracy (AUC = 0.943) in estimating clinical improvement, aiding in the optimization of MVSC in pediatric pneumonia.ConclusionsMVSC enhances the treatment of pediatric pneumonia, with the nomogram optimizing the parameters of the sputum clearance device.